'Hospitals' in times of disasters setting up of surge hospitals as a post-catastrophe response - Rinen, Richard Martin E. (2013)
This paper looked into how the concept of Surge Hospitals can be adapted as a response to the earthquake scenarios reported by the Earthquake Impact Reduction Study of metropolitan Manila (MMEIRS) in 2004. A surge of victims will not be accommodated given the present hospital capacity and their resilience to earthquake. It is assumed that a well designed Curge Hospital will be able to lessen the number of casualties by being able to provide immediate care and treatment to victims. Using the data gathered in the MMEIRS report, hazard and vulnerability maps were used to identify possible "surge zones" within Metro Manila where surge hospitals can be set up. Meanwhile, a review of government plans was also undertaken in order to align possible recommendations with these plans if there are any. The review of the MMEIRS report reveals that the Metropolitan Manila will be geographically separated into four regions namely North, South, East and West. as a response to this separation, the Metropolitan Manila Development Authority organiezed Task Force Rainbow or Oplan Yakal and identified four possible surge zones within the separeated regions where surge hospitals can be set up namely : Veterans Memorial Hospital, Wack Wack Golf Cours, Intramuros Golf Course and Villamor Golf Course. However, no specific plans on how to set up these hospitals are in place. Therefore the study aims to create a conceptual layout of a surge hospital using Veterans Memorial Medical Center as a case study. The concept of surge hospitals were applied to VMMC and this study suggests that it is deemed suitable due to its geographical location, its proximity to support facilities, its general layout and the presence of a large open area to accomodate the surge of victims.
Vita.
Thesis (Master of Architecture)--University of the Philippines Diliman.